If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + -1q + -1(2q + -3) = 0 Reorder the terms: 4q + -1q + -1(-3 + 2q) = 0 4q + -1q + (-3 * -1 + 2q * -1) = 0 4q + -1q + (3 + -2q) = 0 Reorder the terms: 3 + 4q + -1q + -2q = 0 Combine like terms: 4q + -1q = 3q 3 + 3q + -2q = 0 Combine like terms: 3q + -2q = 1q 3 + 1q = 0 Solving 3 + 1q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1q = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 1q = 0 + -3 1q = 0 + -3 Combine like terms: 0 + -3 = -3 1q = -3 Divide each side by '1'. q = -3 Simplifying q = -3
| 3x+1x=15 | | 3x+1x=20 | | 3x+1x=1 | | 7(5-3x)+5(5x-3)= | | 4x^2-2x=80 | | (9y+5)-(7y-3)= | | 66+17y=17 | | 5x=x^2+6 | | x+2x+3x+3=15 | | 2(8+2c)=32 | | 30+5t=80 | | 12x-8=3x+28 | | x+2+3x+3=15 | | 2(5y+6)-4(y-8)= | | 2x^2+2=2 | | n-3/4+n+5/7=5/14 | | 0.5x+x=x | | 0.5x+x=y | | 0.5x+x=1.5x | | 8(r+2)=64 | | (-2ab^2)(5a^3b^4)= | | 5(3c+2)=70 | | -4(1-7a)+5=-8a-39 | | 13+c^2=77 | | 1/8+5/6= | | 3x(6x)= | | -6p-6-15p=5p-20-38 | | 2x^2+10x-126=0 | | 6-3x=6x-8x-6 | | x=6-3y | | (3x+6)2=(5x)2 | | x=18-5y |